Investigation and Analysis of Fuzzy Logic Controller Method on DC-DC Buck-Boost Converter - I Ketut Wiryajati; I Nyoman Wahyu Satiawan; I Made Budi Suksmadana; Bagas Briantara Putra Wiwaha (Jurnal Penelitian Pendidikan IPA, 2025)
This study evaluates the performance of PID, Mamdani FLC, and Sugeno FLC controllers on a DC-DC Buck-Boost Converter to determine their suitability for various control applications. The Buck-Boost Converter, operating in conventional configuration, was modeled using MATLAB/Simulink with parameters: input voltage (12 V), output voltage (24 V), resistor (6.5 Ω), capacitor (1.5 µF), and inductor (10 µH). The converter's switching frequency was set at 20 kHz to ensure stability under varying load and input conditions. PID control was implemented using the Ziegler-Nichols tuning method, while fuzzy controllers utilized Gaussian membership functions and 3×3 fuzzy rule bases. Mamdani employed the centroid defuzzification method, whereas Sugeno used weighted average defuzzification. The simulation tested performance metrics, including rise time, overshoot, output stability, and voltage ripple, under conditions of load and input voltage variations. Results show that PID achieved the fastest rise time (72.452 ms) but exhibited higher sensitivity to input changes. Sugeno provided the most stable output with minimal ripple, while Mamdani demonstrated greater adaptability but less stability compared to Sugeno. Statistical analysis confirmed significant differences in rise time but no differences in overshoot across methods. These findings highlight the strengths of each method, with Sugeno being optimal for stability and precision, PID for fast response, and Mamdani for complex fuzzy logic applications.